ReadWrite Digital : improving student outcomes through educational innovation - Mulloth, Bala; Carden, William, active 2021; Carden, Elizabeth, active 2021 (London : SAGE Publications: SAGE Business Cases Originals, 2021)
ReadWrite Digital is an education technology startup that offers software to K-12 schools in the United States to provide education analytics and personalized education planning. Founded in 2012 by Rob Simms, the current President and CTO, ReadWrite Digital built, developed, and launched two unique products, Integrator and Analytics, providing an end-to-end solution for data collection from disparate systems creating rich analytics for student performance in one place. ReadWrite Digital's software makes student information accessible for data-driven instruction needs and enables educators to be able to discern with clarity the 20% of the K-12 student population (55 million) in the United States that are at risk of not graduating high school. The case will investigate the team's social motivations and shared values that contribute to the organization's goals and vision. Further, the case will discuss the various strategic decisions and dilemmas the organization faced as they sought to maximize impact. Finally, the case will offer some of the lessons learned and potential new directions which ReadWrite Digital had proposed to take.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Educational technology industries -- Case studies